Teaching online a practical guide - Ko, Susan Schor (Routledge, 2017)
an accessible, introductory, practical guide for anyone who teaches online, this edition includes new and expanded information on: massive open online courses (MOOCs); teaching with mobile devices; open educational resources (OER); and learning analytics.